Evaluasi Tegangan-Regangan Dengan Pemodelan Silinder Beton - Ming Narto Wijaya (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2018)
Compressive strength is one of the main parameters in the analysis of concrete behavior. In general, the compressive strength of the concrete will be tested in the laboratory using the Uniaxial Compression Test tool. However, it requires a lot of energy and cost and a long time. For that we need an approach with a simulation of numerical methods that is with finite element method using ABAQUS aids program. Based on the results of numerical analysis, it is concluded that the modeling of concrete elements using ABAQUS element finite aids program can be done by creating 3D solid model, using C3D8R element type and discrete rigid plate as pressure load suppliers. Furthermore, plastic material input is used in the form of Concrete Damaged Plasticity (CDP). While the stress-strain distribution in concrete modeling using ABAQUS auxiliary program shows the distribution according to laboratory test result, especially the elasticity modulus seen from the relationship curve of stress-strain strain. However, there is a difference in the maximum compressive strength achieved between the two tests. Therefore, further analysis is needed to know the properties of the concrete material used in the analysis, and the damage behavior that will influence the input of the material being analyzed.